Hubungan antara Status Gizi dan Sistem Imun Seluler pada Subyek Penyakit Ginjal Kronik Stadium V Hemodialisis di Instalasi Tindakan Hemodialisis RSUP Prof. Dr. R. D. Kandou Manado - Unawekla, Julyan V.; Moeis, Emma Sy.; Langi, Yuanita A. (e-CliniC, 2018)
Abstract: Chronic kidney disease (CKD) is a pathophysiological process with a diverse etiology that causes progressive decrease of renal function and is generally ended with renal failure. Patients with CKD are given low-protein and low-water diets that can affect their nutritional status and immune system. This study was aimed to determine the relationship between nutritional status and cellular immune system in patients with stage V CKD that had hemodialysis perfomed on them at the Installation of Hemodialysis of Prof. Dr. R. D. Kandou Hospital Manado. This was a descriptive analytical study with a cross sectional design. Variables were age, gender, lymphocyte count, body mass index (BMI), and upper arm circumference. There were 30 samples in this study; males (56.7%) were more dominant. The age range was 36-76 years; lymphocyte count range was 1000-4131; IMT range was 16-28.1; and upper arm circumference range was 17-28.50. The Spearman parametric test of the relationship between nutritional status and cellular immune system based on BMI and lymphocyte count obtained a P-value of 0.111 meanwhile the relationship between nutritional status based on upper arm circumference and lymphocytes obtained a P-value of 0.309. Conclusion: There was no relationship between nutritional status (BMI and arm circumference) and cellular immune system (lymphocyte count) in stage V CKD patients that had hemodialysis perfomed on them. Keywords: CKD V-HD, nutritional status, cellular immune systemAbstrak: Penyakit ginjal kronik (PGK) adalah suatu proses patofisiologis dengan etiologi beragam yang mengakibatkan penurunan fungsi ginjal secara progesif dan umumnya berahir dengan gagal ginjal. Pasien PGK diberikan terapi rendah protein dan air sehingga dapat berdampak pada status gizi dan sistem imun pasien. Penelitian ini bertujuan untuk mengetahui hubungan status gizi dengan sistem imun seluler pada subyek PGK stadium V hemodialisis di Instalasi Tindakan Hemodialisis RSUP Prof. Dr. R. D. Kandou Manado. Jenis penelitian ialah deskriptif analitik dengan desain potong lintang. Variabel penelitian ialah usia, jenis kelamin, hasil hitung limfosit, hitung IMT, dan ukuran lingkar lengan atas (LILA). Hasil penelitian mendapatkan 30 sampel dengan jumlah terbanyak ialah laki-laki 17 orang (56,7%), cengan rentang usia 36-76 tahun. Kisaran nilai untuk limfosit ialah 1000-4131; IMT 16-28,1; dan LILA 17-28,50. Uji parametrik Spearman terhadap hubungan antara status gizi berdasarkan IMT dan limfosit mendapatkan P=0,111 sedangkan antara status gizi berdasarkan LILA dan limfosit mendapatkan P=0,309. Simpulan: Tidak terdapat hubungan antara status gizi (IMT dan LILA) dengan limfosit (sistem imun) pada pasien PGK V yang menjalani hemodialisis.Kata kunci: PGK V-HD, status gizi, sistem imun seluler